Effect of the THBS1 Gene Knockout on the Radiation-Induced Cellular Response in a Model System In Vitro - Savchenko R. R. Renata Renatovna; Vasiljev S. A. Stanislav Anatoljevich; Fishman V. S. Veniamin Semenovich; Sukhikh E. S. Evgeniya Sergeevna; Sukhikh L. G. Leonid Grigorievich; Murashkina A. A. Anastasiya Aleksandrovna; Lebedev I. N.. Igor Nikolaevich (2020, 2020)
Title screen